Вредители интродуцированных растений защищенного грунта в Донецком ботаническом саду НАН Украины - Попов, Г.В.; Коваленко, В.М. (Промышленная ботаника, 2002)
The results of investigation on fauna of pests of the plants introduced into the conservatories of the Donetsk botanical gardens, Nat. Acad. Sci. of Ukraine are given. The pests fauna numbers 16 species, namely 1 Nematoda , 1 Mollusca, 13 Arthropoda, 1 Mammalia species, the principal trophic interrelations of which are considered. Taxonomic diversity of the fauna is relatively high that is seemingly a result of its long-term formation and considerable diversity of the plants species introduced into the conservatories of the Botanical gardens.